Phenolic content, antioxidant and antibacterial activities of Plectranthus rotundifolius tuber extracts. Issue 2 (3rd April 2018) - Murthy, H. N; Herlekar, V. V; Joseph, K. S; Payamalle, S; Shinde, S
ABSTRACT: The phenolic and flavonoid concentration and antioxidant and antibacterial activities of Plectranthus rotundifolius tuber extracts in petroleum ether, chloroform, and methanol were determined. The methanol extracts had the highest recovery and demonstrated the highest antioxidant potential and efficacy against the clinical bacterial strains tested as evident from the minimum inhibitory concentrations.